Asterisks on solidarity (Journal of Parents and Teachers, 2026)
Here are some questions to consider regarding one’s personal stance on the value of solidarity, which must not only be proclaimed but also experienced by others. In a world where competitiveness takes precedence, solidarity becomes a challenge for education.
Keywords: solidarity; value; humanity